Analysis of factors that influence on organization of educational and production practice in preparation of pharmacy specialists - Barkovska, Oksana; Ogar’, Svetlana; Rogulia, Olga; Havrysh, Nataliia (ScienceRise: Pharmaceutical Science, 2017)
The aim: The aim of the study is to group and analyze external and internal factors that influence on the process of organization of educational and production practices as a component of professional training of specialists in the system of higher pharmaceutical education, and the development of a set of recommendations for its improvement. Methods: To achieve the goal methods of scientific analysis were used, in particular generalization, comparison, content analysis, system and logical methods. Results: The relevance of the study of the factors influencing the process of organization of teaching and production practice by the applicants of higher pharmaceutical education is proved. A grouping of internal and external factors is performed and the essence of them is revealed on the basis of classification. A set of measures aimed at improving the organization of educational and production practices at higher educational institutions (HEIs) was developed and recommended. Conclusion: The main factors determining the process of organization of practice in higher educational institutions are outlined. The external and internal factors influencing the process of organization of educational and production practice are analyzed. In order to ensure the proper quality of practical training, a set of measures is recommended to improve the organization of educational and production practices in the pharmaceutical education system